On demand treatment and home therapy of hereditary angioedema in Germany - the Frankfurt experience - Aygören-Pürsün, Emel (BioMed Central, 2010)
BACKGROUND: Manifestation of acute edema in hereditary angioedema (HAE) is characterized by interindividual and intraindividual variability in symptom expression over time. Flexible therapy options are needed. METHODS: We describe and report on the outcomes of the highly individualized approach to HAE therapy practiced at our HAE center in Frankfurt (Germany). RESULTS: The HAE center at the Frankfurt University Hospital currently treats 450 adults with HAE or AAE and 107 pediatric HAE patients with highly individualized therapeutic approaches. 73.9% of the adult patients treat HAE attacks by on-demand therapy with pasteurized pd C1-INH concentrate, 9.8% use additional prophylaxis with attenuated androgens, 1% of the total patient population in Frankfurt has been treated with Icatibant up to now. In addition adult and selected pediatric patients with a high frequency of severe attacks are instructed to apply individual replacement therapy (IRT) with pasteurized pd C1-INH concentrate. Improvement on Quality of Life items was shown for these patients compared to previous long-term danazol prophylaxis. Home treatment of HAE patients was developed in the Frankfurt HAE center in line with experiences in hemophilia therapy and has so far been implemented over a period of 28 years. At present 248 (55%) of the adult patients and 26 (24%) of the pediatric patients are practicing home treatment either as on demand or IRT treatment. CONCLUSIONS: In conclusion, the individualized home therapies provided by our HAE center, aim to limit the disruption to normal daily activities that occurs for many HAE patients. Furthermore, we seek to optimize the economic burden of the disease while offering a maximum quality of life to our patients.